Concurrent impact evaluation of lockdown measures on COVID-19 positivity in three states of India - Choudhury, Lincoln Priyadarshi; Jammy, G. R.; Pant, Rashmi (International Journal Of Community Medicine And Public Health, 2020)
Background: In response to the COVID pandemic, many preventive steps have been undertaken in the India, including lockdown measures. The objective of the study was to analyze the impact of lockdown on COVID-19 epidemic. Methods: We used quasi-experimental interrupted time series analysis using reported data from 17 March 2020 to 14 April 2020 with effective time interruption on 3 April 2020. We used publicly available data from three states to calculate the pre and post lockdown period COVID-19 test positivity. Results: The lockdown was able to reduce the infections cases in all three states. The trend of positivity changed to negative for Tamil Nadu and Odisha and accelerated upward in Kerala. The trend changes for positivity were statistically significant for two states (Tamil Nadu and Odisha). In comparison to counterfactual, on 13 April 2020, the predicted relative change in COVID-19 positivity was maximum for the state of Odisha (108%), followed by Tamil Nadu (85%) and Kerala (78%) respectively. Conclusions: The lockdown measurements were observed to be effective in the three states studied. However, the quantity of change varied from state to state. Policymakers and public health scientists can consider these findings ad methodology for future action.